La déforestation baisse en Amazonie. Vraiment ? - François-Michel Le Tourneau (EchoGéo)
The unexpected fall of deforestation in the Brazilian Amazon in 2022 has shown that deforestation phenomena are complex and that for many observers it is difficult to find their way in statistics and geospatial databases that are produced using different methodologies and distinct definitions of what deforestation is and considering in diverging ways various types of environmental damages. In this context, this paper attempts to replace recent figures in a broader context spatially (considering the whole Amazon region beyond Brazil), temporally (looking at the phenomena since the 1980s) and thematically (presenting several sources of data). To do so, we first present the data that are available to the public about deforestation, distinguishing their (sometimes apparently contradictory) characteristics and underlining the Amazon’s inherent ecological and geographical complexity. In a second part, we describe the history of deforestation since 1985, first at the level of the whole basin (or pan-Amazonia) and then focusing on the Brazilian Amazon. Last, as to complete our panorama of the question of deforestation, we present quickly the causes of deforestation and the principal policies of the governments to face it, as well as the consequences of deforestation at the local, regional and global scales.